The Feasibility of E-Modules Based on Flipbook Pdf Professional to Improve Student Learning Outcomes on Work and Energy Material - Siskia Charina Wadah; Sarah Miriam; Dewi Dewantara; Suyidno Suyidno (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2022)
Digital-based learning has become a trend in 21st-century education. However, most teaching materials are currently in the form of printed books which tend to be monotonous and less attractive, thus affecting low student learning outcomes. This research aims to produce a professional PDF flipbook-based e-module to improve student learning outcomes on work and energy material. The development model used is ADDIE. The implementation test used a one-group pre-test and post-test design on 34 students of class X MIPA of one of the high schools in Banjarmasin, South Kalimantan, Indonesia. Data were obtained through e-module validation instruments and student response questionnaires. The results obtained content and construct validity values of e-modules were 3.36 and 3.31, respectively, with valid categories. In addition, student responses amounted to 3.03 in the practical category. Thus, the developed e-module is feasible for improving student learning outcomes.